Assessment Of Human Reliability Using The Sherpa And Heart Approach To Container Crane Operation Activities. (Case Study PT Petikemas Surabaya) - Asri Dwi Puspita; Anthon De Fretes (IQTISHADequity jurnal MANAJEMEN, 2022)
The port is a sea transportation infrastructure that plays an essential role in the growth of industry and trade. Ports are required to be able to serve operational activities 24/7, meaning 24 hours and 7 full days. Container Crane mainly carries out loading/unloading activities for containers (container B/M) for activities at the wharf. From 2015 to 2021, there have been accidents at PT TPS, as many as 1,074 incidents with an average annual incidence + 175 accident incidents. Errors from operating equipment or human error mainly cause accidents. This study aims to analyze human reliability assessment on CC operations using the Systematic Human Error Reduction and Prediction (SHERPA) and Human Error Assessment and Reduction Technique (HEART) methods in conducting research using primary data through interviews with expert judgment. Based on the approach to using this method, it is hoped that recommendations can be made to control and prevent work accidents resulting from human error. Based on the results of error identification using the SHERPA method in CC operation, 14 error sub-tasks result in work accidents, 13 work sub-tasks must be recovered immediately, there are 2 sub-tasks with high probability, and there are 13 sub-tasks with a critical level of loss Not acceptable.